Synthesis and evaluation of porphyrin glycoconjugates varying in linker length: preliminary effects on the photodynamic inactivation of Mycobacterium smegmatis - Dixon, Charlie F. (RSC Adv, 2021)
Porphyrins have served as common photosensitizing agents in photomedicine due to their unique properties and broad therapeutic potential. While photodynamic therapy (PDT) offers a promising avenue for novel drug development, limitations in application due to selectivity, and the inherent hydrophobicity and poor solubility of porphyrins and other organic photosensitizers has been noted. Porphyrin glycoconjugates have recently gained attention for their potential to overcome these limitations. However, little has been done to explore the effects of the linker between the carbohydrate and porphyrin analog. Here we report the synthesis of over 30 new carbohydrate–porphyrin conjugates which vary in the nature of the sugar (Gal, Glc, GalNAc, GlcNAc, Lac and Tre) and the distance between the porphyrin macrocycle and the carbohydrate. Porphyrin glycoconjugates were synthesized in three steps from a readily available meso-brominated diphenylporphyrin analog by (i) C–O coupling of an appropriate TMS-protected alkynol consisting of two to six carbon spacers (ii) removal of the TMS protecting group, and (iii) CuAAC conjugation with an appropriate glycosyl azide. First studies with trehalose-based glycoporphyrins and M. smeg were used to determine the effects of the linker in photodynamic inactivation (PDI) studies. Preliminary results demonstrated an increase in photodynamic inactivation with a decrease in linker length. Investigations are underway to determine the mechanism for these results.